Drug-associated serotonin syndrome in elderly patients: a comprehensive disproportionality analysis based on the FAERS database - Li, Xiaozhi; Wen, Xiaofen; Fu, Hongbo; Hong, Xiaobing; Lin, Danxia; Li, Xiaoyan; Liang, Zhikun; Wang, Mengna; Yu, Xihui; Zhou, Yanqiong; Luo, Xiajiong (Frontiers in Pharmacology, 2025)
BackgroundThis study aims to identify drugs associated with serotonin syndrome in elderly patients by utilizing the FDA Adverse Event Reporting System (FAERS), to provide evidence-based references for safe clinical medication practices.MethodsThis study analyzed data extracted from the FAERS covering the period from Q1 2004 to Q1 2025, with the objective of identifying drugs associated with serotonin syndrome in elderly patients. Disproportionality analysis was utilized to detect potential drug-associated signals, and sensitivity analyses were performed to evaluate the stability and strength of serotonin syndrome signals associated with these drugs. Time-to-onset (TTO) analysis was conducted to investigate factors influencing the clinical presentation of serotonin syndrome.ResultsDisproportionality analysis identified 68 drugs associated with serotonin syndrome in elderly patients. Among the drugs with positive signals, the most frequently reported category associated with serotonin syndrome in elderly patients was nervous system drugs, followed by antiinfectives for systemic use, alimentary tract and metabolism drugs, musculo-skeletal system drugs, dermatologicals, and respiratory system drugs. Sensitivity analyses confirmed that most positive signals remained robust. TTO analysis revealed that drug-associated serotonin syndrome onset occurred earlier in elderly female patients.ConclusionDrug-associated serotonin syndrome risk is elevated among elderly patients. Prompt identification and discontinuation of the causative drugs are crucial for the effective management of serotonin syndrome. In clinical practice, the risk of drug-associated serotonin syndrome should be taken into account to optimize pharmacotherapy.